2023
DOI: 10.1093/aob/mcad188
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of grapevine resilience to a vascular disease: investigating stem radial growth, xylem development and physiological acclimation

Ninon Dell’Acqua,
Gregory A Gambetta,
Sylvain Delzon
et al.

Abstract: Background and Aims Plant vascular diseases significantly impact crop yield worldwide. Esca is a grapevine vascular disease found globally in vineyards which causes a loss of hydraulic conductance due to the occlusion of xylem vessels by tyloses. However, the integrated response of plant radial growth and physiology in maintaining xylem integrity in grapevine expressing esca symptoms remains poorly understood. Methods We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…There have been many studies of the impact of esca disease on grapevine physiology, including plant growth (Gramaje et al ., 2010; Dell’Acqua et al ., 2023), photosynthesis, water relations (Magnin-Robert et al ., 2011; Bortolami et al ., 2021a,b), and phenology (Andreini et al ., 2013), but very little effort has, as yet, been devoted to the opposite issue: the ecophysiological traits predicting esca incidence or severity. Here, we found that a low incidence of esca appeared to be associated with high water use efficiency and low vigour at the cultivar scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies of the impact of esca disease on grapevine physiology, including plant growth (Gramaje et al ., 2010; Dell’Acqua et al ., 2023), photosynthesis, water relations (Magnin-Robert et al ., 2011; Bortolami et al ., 2021a,b), and phenology (Andreini et al ., 2013), but very little effort has, as yet, been devoted to the opposite issue: the ecophysiological traits predicting esca incidence or severity. Here, we found that a low incidence of esca appeared to be associated with high water use efficiency and low vigour at the cultivar scale.…”
Section: Discussionmentioning
confidence: 99%
“…Foliar symptoms are associated with xylem hydraulic failure and impaired photosynthesis (Bortolami et al ., 2019, 2021a; Ouadi et al ., 2021; Dell’Acqua et al ., 2023). The incidence of esca foliar symptoms is probably affected by multiple factors (as reviewed in Claverie et al ., 2020), including plant age, pedoclimatic conditions, viticulture practices, the plant- and soil-associated microbiota, and the plant material.…”
Section: Introductionmentioning
confidence: 99%